Two-dimensional photonic crystals increasing vertical light emission from Si nanocrystal-rich thin layers - Ondič, Lukáš; Varga, Marian; Pelant, Ivan; Kromka, Alexander; Hruška, Karel; Elliman, Robert G. (Beilstein Journal of Nanotechnology, 2018)
We have fabricated two-dimensional photonic crystals (PhCs) on the surface of Si nanocrystal-rich SiO2 layers with the goal to maximize the photoluminescence extraction efficiency in the normal direction. The fabricated periodic structures consist of columns ordered into square and hexagonal pattern with lattice constants computed such that the red photoluminescence of Si nanocrystals (SiNCs) could couple to leaky modes of the PhCs and could be efficiently extracted to surrounding air. Samples having different lattice constants and heights of columns were investigated in order to find the configuration with the best performance. Spectral overlap of the leaky modes with the luminescence spectrum of SiNCs was verified experimentally by measuring photonic band diagrams of the leaky modes employing angle-resolved spectroscopy and also theoretically by computing the reflectance spectra. The extraction enhancement within different spatial angles was evaluated by means of micro-photoluminescence spectroscopy. More than 18-fold extraction enhancement was achieved for light propagating in the normal direction and up to 22% increase in overall intensity was obtained at the spatial collection angle of 14°.
Keywords: leaky modes; photoluminescence; photonic crystals; silicon nanocrystals